Electronic structure and magnetic properties of rare-earth RM₂ and RM₃ compounds - Baranovskiy, A.E.; Grechnev, G.E.; Panfilov, A.S.; Svechkarev, I.V. (Functional Materials, 2004)
Ab initio calculations of the electronic structure and magnetic properties are carried out for the ferromagnetic Gd0₂ compounds (M = Mg, Al, Fe, Co, Ni, Rh, lr, Pt), and also for the La(ln₁-ₓSnₓ)₃ system. Pressure effects on the band structure and magnetic properties of Gd0₂ have been evaluated and supplemented experimentally by magnetic susceptibility x measurements under pressure in the paramagnetic phase. The peculiarities of χ(x) in La(ln₁-ₓSnₓ)₃ alloys are found to originate from the band degeneracy points near the Fermi level. Experimental χ(x) data are analyzed in the framework of modern band and orbital magnetism theories. Проведены расчеты из первых принципов электронной структуры и магнитных свойств ферромагнитных соединений GdMV₂ (M = Mg, Al, Fe, Co, Ni, Rh, lr, Pt) и системы La(ln₁-xSnx)₃. Эффекты давления на зонную структуру и магнитные свойства GdMV₂ изучены теоретически, а также экспериментально на основе измерений магнитной восприимчивости x под давлением в парамагнитной фазе. Показано, что особенность χ(x) в сплавах La(ln₁-xSnx)₃ обусловлена наличием точки вырождения зон в окрестности уровня Ферми. Анализ экспериментальной зависимости χ(x) проведен в рамках современных теорий орбитального и зонного магнетизма. Зроблєні тєорєтичні розрахунки електронної структури та магнітних властивостей феромагнітних сполук GdM₂ (M = Mg, Al, Fe, Co, Ni, Rh, lr, Pt) та системи La(ln₁-xSnx)₃ . Вплив тиску на зонну структуру та магнітні властивості Gd0₂ сполук було вивчено теоретично та експериментально, грунтуючись на вимірах магнітної сприятливості x під тиском у парамагнітній фазі. Знайдено, що особливість χ(x) у сплавах La(ln₁-xSnx)₃ визначається виродженими електронними станами біля рівня Фермі. Аналіз експериментальної залежності χ(x) був проведений за допомогою сучасних теорій зонного та орбітального магнетизму.